2020
DOI: 10.1038/s41522-020-0132-3
|View full text |Cite
|
Sign up to set email alerts
|

IolR, a negative regulator of the myo-inositol metabolic pathway, inhibits cell autoaggregation and biofilm formation by downregulating RpmA in Aeromonas hydrophila

Abstract: Aeromonas hydrophila is the causative agent of motile Aeromonad septicemia in fish. Previous studies have shown that the myoinositol metabolism is essential for the virulence of this bacterium. IolR is a transcription inhibitor that negatively regulates myoinositol metabolic activity. While in the process of studying the inositol catabolism in A. hydrophila Chinese epidemic strain NJ-35, we incidentally found that ΔiolR mutant exhibited obvious autoaggregation and increased biofilm formation compared to the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 34 publications
0
22
2
Order By: Relevance
“…Autoaggregation can be the indirect consequence of a secreted factor mediating aggregation indirectly by connecting other surface factors [28]. Proteinase K treatment more commonly alters or completely obliterates autoaggregation compared with sodium periodate ( polysaccharide removal) and DNase1 (extracellular DNA removal) treatment [29][30][31]. However, polysaccharides as well extracellular DNA, released during autolysis can mediate autoaggregation.…”
Section: Secreted Macromoleculesmentioning
confidence: 99%
“…Autoaggregation can be the indirect consequence of a secreted factor mediating aggregation indirectly by connecting other surface factors [28]. Proteinase K treatment more commonly alters or completely obliterates autoaggregation compared with sodium periodate ( polysaccharide removal) and DNase1 (extracellular DNA removal) treatment [29][30][31]. However, polysaccharides as well extracellular DNA, released during autolysis can mediate autoaggregation.…”
Section: Secreted Macromoleculesmentioning
confidence: 99%
“…It was found that an overproduction of Ah Lap (named against convention within the study as RmpA) was responsible for this new phenotype, adding Ah Lap to the growing list of RTX adhesins vital to biofilm formation ( Guo et al, 2017 , Hinsa et al, 2003 , Martínez-Gil et al, 2010 , Syed et al, 2009 ). While deletions of Ah Lap removed the hyper biofilm-forming phenotype as expected, so too did the removal of Ca 2+ from the solution via chelating agents ( Dong et al, 2020 ). This result mirrors other such experiments on RTX adhesin-mediated behaviour, like studies on the RTX adhesin SiiE in Salmonella enterica , where the removal of calcium greatly reduced invasion of the bacteria into polarized epithelial cells ( Peters et al, 2017 ).…”
Section: Discussionmentioning
confidence: 81%
“…Several such cases have been reported ( D’Auria et al, 2008 , Guo et al, 2017 , Wrobel et al, 2018 ), and likely many more have yet to be caught. For instance, only a single repeat is reported in the Ah Lap sequence from the NJ-35 strain ( Dong et al, 2020 ), which could be an underestimate.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations